Betacellulin regulates schwann cell proliferation and myelin formation in the injured mouse peripheral nerve. Issue 4 (31st January 2017) - Vallières, Nicolas; Barrette, Benoit; Wang, Linda Xiang; Bélanger, Erik; Thiry, Louise; Schneider, Marlon R.; Filali, Mohammed; Côté, Daniel; Bretzner, Frédéric; Lacroix, Steve
Abstract : When a nerve fiber is cut or crushed, the axon segment that is separated from the soma degenerates distal from the injury in a process termed Wallerian degeneration (WD). C57BL/6OlaHsd‐ Wld S (Wld S ) mutant mice exhibit significant delays in WD. This results in considerably delayed Schwann cell and macrophage responses and thus in impaired nerve regenerations. In our previous work, thousands of genes were screened by DNA microarrays and over 700 transcripts were found to be differentially expressed in the injured sciatic nerve of Wld S compared with wild‐type (WT) mice. One of these transcripts, betacellulin (Btc), was selected for further analysis since it has yet to be characterized in the nervous system, despite being known as a ligand of the ErbB receptor family. We show that Btc mRNA is strongly upregulated in immature and dedifferentiated Sox2 + Schwann cells located in the sciatic nerve distal stump of WT mice, but not Wld S mutants. Transgenic mice ubiquitously overexpressing Btc (Tg‐Btc) have increased numbers of Schmidt‐Lantermann incisures compared with WT mice, as revealed by Coherent anti‐Stokes Raman scattering (CARS). Tg‐Btc mice also have faster nerve conduction velocity. Finally, we found that deficiency in Btc reduces the proliferation of myelinating Schwann cells after sciatic nerve injury, while Btc overexpression induces Schwann cell proliferation and improves recovery of locomotor function. Taken together, these results suggest a novel regulatory role of Btc in axon‐Schwann cell interactions involved in myelin formation and nerve repair. GLIA 2017 GLIA 2017;65:657–669 Main Points: Betacellulin is upregulated in Schwann cells after peripheral nerve injury in mice. Betacellulin overexpression induces Schwann cell proliferation and improves locomotor recovery after sciatic nerve injury. Betacellulin overexpression leads to increase in the number of Schmidt‐Lantermann incisures and nerve conduction velocity.